Drawing a Line in the Sand: Bioengineering as Conservation in the Face of Extinction Debt - Wodak, Josh (Queensland Review, 2012)
What conservation could possibly become commensurate with the rates of human-induced biophysical change unfolding at the advent to the Sixth Extinction Event? Any such conservation would require time-critical interventions into both ecosystems and evolution itself, for these interventions would also require domains of risk and ethics that shatter normative understandings of conservation. Yet a line appears to have been drawn in the sand against such experimental conservation. Holding the line will retain conservation practices that are null and void against the extinction debt facing multitudes of species. Crossing the line would invoke scales of bioengineering that appear abhorrent to normative morality. This article explores the question of whether this line in the sand could, and should, be crossed through a detailed case study of current and proposed conservation for endangered Chelonia mydas sea turtles on Raine Island, a small coral cay on the Great Barrier Reef in Australia. Chelonia mydas and Raine Island are presented as synecdoche for conservation across diverse species across the world because turtles are among the most endangered of all reptiles and Raine Island is the largest and most important rookery in the world for this species. With such lines disappearing under the rising seas, the article contemplates the unthinkable questions that our current situation demands we ask, and perhaps even try to answer.